Normothermic kidney preservation - Weissenbacher, A (2018)
The thesis describes the development of a transportable normothermic kidney preservation device which is able to perfuse discarded human and porcine kidneys for up to 24 hours for the very first time. Recirculation of the urine to facilitate maintenance of perfusate volume and homeostasis is a novel approach. Utilisation of this perfusion device could enable viability assessment, decrease organ discard rate and improve transplantation logistics. Thirty-six clinically declined human kidneys were perfused, 19 from donors after brain stem death and 17 from donors after circulatory death: n=4 kidneys were perfused using Ringer’s lactate to replace excreted urine volume, and n=32 using urine recirculation. In all cases, normothermic perfusion either maintained or slightly improved the histopathologically assessed tubular condition, achieved physiological arterial flow levels and effective urine production. Biomarkers, neutrophil gelatinase-associated lipocalin (NGAL), kidney injury molecule-1 (KIM-1) and liver fatty acid-binding protein (L-FABP) were detected and quantified in the perfusates with and without urine recirculation. NGAL could be promising for clinical use, as it was inversely correlated with median arterial flow. Only kidneys with urine recirculation were readily perfused up to 24 hours and exhibited physiological perfusate sodium levels, whilst kidneys without urine recirculation achieved reduced normothermic perfusion time and significantly higher perfusate sodium. Metabolomics analyses of perfusate samples detected urea and two sugars as the main difference between kidneys with and without urine recirculation. Proteomics analyses not only revealed that human kidneys have become metabolically active during normothermic perfusion, but they also detected that damage-associated molecular patterns known to contribute to ischaemia-reperfusion-injury, were significantly downregulated in biopsies from kidneys with urine recirculation compared to kidneys without. As a final part, porcine perfusion studies were performed with the aim to revisit the findings obtained during the human experiments and to render a valid comparison between urine recirculation and urine replacement in undamaged kidneys.